1985
DOI: 10.1161/01.str.16.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral haemorrhage and angiographic beading following ingestion of catecholaminergics.

Abstract: SUMMARY We report two cases of serious intracerebral haemorrhage occurring in young women following their first use of oral medications containing catecholaminergic agents (phenylpropanolamine in combination with ephedrine or pseudoephedrine). Both women were previously well, and there was no evidence for systemic vasculitis, coagulopathy, aneurysm or arteriovenous malformation. Angiography in both cases, performed approximately forty hours following drug ingestion, revealed the beading pattern typical of that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…9 Intravenous methamphetamine has been shown to produce transient decreased vessel diameter in rhesus monkeys within 1 hour of administration. 10 Arteriographic changes consistent with vasculitis have been reported with other recreational drugs, including phenylpropanolamine, 11 -13 ephedrine, 14 pseudoephedrine, 15 and heroin. 16 Previous reports of vasculitis associated with drug abuse have been flawed by a lack of pathological verification and the frequent history of multiple-drug use.…”
Section: Discussionmentioning
confidence: 74%
“…9 Intravenous methamphetamine has been shown to produce transient decreased vessel diameter in rhesus monkeys within 1 hour of administration. 10 Arteriographic changes consistent with vasculitis have been reported with other recreational drugs, including phenylpropanolamine, 11 -13 ephedrine, 14 pseudoephedrine, 15 and heroin. 16 Previous reports of vasculitis associated with drug abuse have been flawed by a lack of pathological verification and the frequent history of multiple-drug use.…”
Section: Discussionmentioning
confidence: 74%
“…2) The mechanisms of action of amphetamines as a cause of ICH may involve acute arterial inflammation (arteritis) and a sharp rise in blood pressure due to the sympathomimetic effect. 4,6,7,10) Most cases of ICH have occurred in patients with a known clinical history of amphetamine abuse. 4,6,7,10) The onset of ICH is usually acute, i.e., within several hours after the use of amphetamines, and the frequency of drug abuse increases the risk of the hemorrhage, although some patients sustained ICH after their initial use of amphetamines.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7,10) Most cases of ICH have occurred in patients with a known clinical history of amphetamine abuse. 4,6,7,10) The onset of ICH is usually acute, i.e., within several hours after the use of amphetamines, and the frequency of drug abuse increases the risk of the hemorrhage, although some patients sustained ICH after their initial use of amphetamines. 4,6,7,10) To raise the suspicion of illegal drugs as causative agents in young, previously healthy patients presenting with progressive neurological deficits is often difficult, especially if no family members or witnesses are available to report the possible use of such drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catecholamines also decrease myocardial refractoriness, which can predispose the heart to arrhythmias, and indeed ventricular arrhythmias have been reported in pregnant women using over-the-counter decongestants (Onuigbo and Alikhan, 1998) as well as in others using Ephedra alkaloids recreationally (Andraws et al, 2005). Cases of stroke in connection with the use of ephedrine and related compounds have been reported (Kaberi-Otarod et al, 2002;Mourand et al, 1999;Stossel et al, 1985;Vahedi et al, 2000;Yin, 1990). Morgenstern et al (2003) reported a case-control study examining the risk of hemorrhagic stroke associated with these compounds.…”
Section: Adverse Effectsmentioning
confidence: 99%